Merawat “Hutan Kehidupan” Berbasis Budaya Keagamaan Moderat: Caring for the “Forest of Life” Based on a Moderate Religious Culture - Mubarak, Mubarak; Said, Nurman; Saidy, Emily Nur; Zulfahnur, Zulfahnur (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The Battang Protected Forest Area is the source of life for the surrounding community. Therefore, it is essential to preserve and care for forests based on moderate religious culture as a form of implementation of worship to God. This research and community service activity uses the Community Based Research (CBR) model—data collection using FGD, Mapping, and Interview. The data were analyzed using qualitative analysis of the Miles and Huberman model. The findings show that the community knows various characteristics of forests in Battang. However, some communities consider the forest in Battang a customary forest. From the assistance based on cultural and religious values, the community can recognize human relations with forests that have existed for generations, such as how to cultivate agriculture and find places to settle. This service research implies that the community realizes the importance of caring for forests that stick to customs and religion.